2004
DOI: 10.1007/s11940-004-0021-8
|View full text |Cite
|
Sign up to set email alerts
|

Marine neurotoxins: Envenomations and contact toxins

Abstract: Familiarity with the appearance and habitat of venomous sea creatures, the location of their stinging apparatus, and surveillance of population concentrations within recreational waters are essential in avoiding envenomations. Compared with the thermo-stable low molecular weighted ingestible seafood toxins, venomous toxins are often large molecular weight proteins and many are heat labile, which provides opportunity for therapeutic intervention. Heat therapy may denature the toxins, and provide immediate relie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 34 publications
0
37
0
1
Order By: Relevance
“…Not all species of jellyfish are poisonous even though they all have stinging cells, and the geographical distribution of venomous ones can be varied depending on the species. In the case of severe stings, however, the victims may show diverse responses, including fever, respiratory distress, and gastrointestinal symptoms of increased secretions, nausea, emesis, abdominal colic, and diarrhea [22], [23]. Major life threatening symptoms are cardiovascular instability with syncope, respiratory insufficiency, and anaphylaxis, which may result in the death of victims [21], [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…Not all species of jellyfish are poisonous even though they all have stinging cells, and the geographical distribution of venomous ones can be varied depending on the species. In the case of severe stings, however, the victims may show diverse responses, including fever, respiratory distress, and gastrointestinal symptoms of increased secretions, nausea, emesis, abdominal colic, and diarrhea [22], [23]. Major life threatening symptoms are cardiovascular instability with syncope, respiratory insufficiency, and anaphylaxis, which may result in the death of victims [21], [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…Carrette [70] appropriately concluded that if the sting is minor or unnoticed and systemic symptoms have already developed, heat application may be useless. In some cases, however, heat is included in the management of C. fleckeri envenomations [73]. A RCT is currently underway evaluating the effectiveness of heat in treating C. fleckeri envenomation (Seymour JE, personal communication).…”
Section: 2 Cubozoans Speciesmentioning
confidence: 99%
“…As espécies de caramujos marinhos com alvos já estabelecidos incluem C. magus, C. aulicus, C. regius, C. purpurascens, C. imperialis e C. geographus (OLIVERA & TEICHERT, 2007). O veneno do caramujo marinho do gênero Conus causa acidente grave, com quadros de dor intensa, seguida de parestesia generalizada, além da paralisia neuromuscular e óbito por insufi ciência respiratória relatados em humanos (WATTERS & STOMMEL, 2004).…”
Section: Toxinas De Caramujos Marinhosunclassified